1994
DOI: 10.1038/bjc.1994.196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the therapeutic gain in the treatment of human osteosarcoma microcolonies in vitro with 211At-labelled monoclonal antibody

Abstract: Summary Microcolonies were obtained by culturing cells of two human osteosarcoma lines (OHS and KPDX) and one human melanoma line (WIX-c) for either 24 or 72 h. The microcolonies were treated with either a-particle radiation emitted by the 2"'At-labelled monoclonal antibody (MAb) Compounds labelled with the a-particle emitter 2"'At have for some time been preclinically investigated as a means for irradiation of tumour cells (Bloomer et al., 1981;Brown et al., 1981;Vaughan et al., 1981Vaughan et al., , 1982… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…6,19 In such cases, RT is often vari- 21 Similarly, a separate study showed that the dose necessary to achieve 50% survival (D50%) in osteosarcoma cell lines was, in fact, much lower than the D50% of cell lines derived from human melanomas, which are also frequently viewed as radioresistant. 22 Furthermore, a clear dose-response relation with local tumor control was not established in our study or in the studies by DeLaney et al 7 and Schwarz et al, 19 yet this relationship may be more apparent with proton therapy. 8 Although the clinical outcomes in patients with osteosarcomas managed with definitive chemoradiation are poor and the LF rates of tumors managed with surgery and RT are inferior to those for tumors managed with surgical resection alone, it is likely that this result is, at least in part, influenced by the more aggressive tumor biology manifested in tumors for which RT is ultimately employed.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…6,19 In such cases, RT is often vari- 21 Similarly, a separate study showed that the dose necessary to achieve 50% survival (D50%) in osteosarcoma cell lines was, in fact, much lower than the D50% of cell lines derived from human melanomas, which are also frequently viewed as radioresistant. 22 Furthermore, a clear dose-response relation with local tumor control was not established in our study or in the studies by DeLaney et al 7 and Schwarz et al, 19 yet this relationship may be more apparent with proton therapy. 8 Although the clinical outcomes in patients with osteosarcomas managed with definitive chemoradiation are poor and the LF rates of tumors managed with surgery and RT are inferior to those for tumors managed with surgical resection alone, it is likely that this result is, at least in part, influenced by the more aggressive tumor biology manifested in tumors for which RT is ultimately employed.…”
Section: Discussioncontrasting
confidence: 67%
“…For example, Larsen et al demonstrated that the α and β values, derived from clonogenic cell survival curves of three osteosarcoma cell lines, were similar to values obtained for cell lines derived from human tumors that are frequently cured with RT . Similarly, a separate study showed that the dose necessary to achieve 50% survival (D50%) in osteosarcoma cell lines was, in fact, much lower than the D50% of cell lines derived from human melanomas, which are also frequently viewed as radioresistant . Furthermore, a clear dose‐response relation with local tumor control was not established in our study or in the studies by DeLaney et al and Schwarz et al, yet this relationship may be more apparent with proton therapy .…”
Section: Discussionmentioning
confidence: 99%
“…When higher specific activity preparations were used, the specific mAb was up to 80 times more potent than controls in reducing clonogenic potential, reaching D 0 (reduction in survival to 37%) at an average of 40 211 At atoms bound per cell. Evaluation of cytotoxicity in microcolonies consisting of 10-15 cells in planar arrays revealed that the cytotoxicity of 211 At-labeled TP-3 was up to 4 times higher than that of 211 At-labeled bovine serum albumin control [88]. In both assay formats, the selectivity of cell kill with 211 At-labeled TP-3 were highly dependent on the specific activity of the mAb, underscoring the need for maximizing this parameter in order to achieve optimum cell killing.…”
Section: In Vivo Studies With 211 At-labeled Mabs and Mab Fragmentsmentioning
confidence: 87%
“…Higher specific activity preparation demonstrated 80-fold higher potency compared to controls with a D 0 equivalent to 40 211 At atoms bound per cell. The cytotoxicity of 211 At-TP3 also was determined using two osteosarcoma cell lines and one melanoma cell line in microcolonies consisting of 10-15 cells in planar arrays [155]. The therapeutic gain factors (TGF), calculated for survival levels, were in the range of 1.3 ± 0.4–4.5 ± 0.7 for 211 At-TP3 and was 1.6-fold higher in the case of the antigen-rich OHS cell line compared to that of the antigen-poor KPDX cell line.…”
Section: Antibodies and Their Engineered Fragmentsmentioning
confidence: 99%